GEOCRYOLOGICAL CONDITIONS OF THE FORMATION OF GIANT SPRING AUFEIS AT THE ANMANGYNDA RIVER (MAGADAN REGION) ACCORDING TO GEOPHYSICAL DATA - V. V. Olenchenko; O. M. Makarieva; A. A. Zemlianskova; A. A. Ostashov; A. S. Kalganov; A. V. Chekryzhov (Геодинамика и тектонофизика)
Giant aufeis fields, common in the Northeast of Russia, are the indicators of water exchange processes in cryosphere. The development of ideas about icing processes is relevant both from the fundamental point of view of studying the permafrost evolution, and from the practical point of view – for the development of aufeis hazard measures. The aufeis in the Anmangynda River basin (aufeis glade area 7 km2) is considered representative of the region, and its studies have been carried out since 1962. In 2022, during the period of maximum thawing of the active layer Electrical Resistivity Tomography (ERT) soundings were carried out at the aufeis glade aiming to identify underchannel taliks and flooded fault zones in bedrock, including local areas of groundwater discharge. It was found that within the main river channels there are underchannel taliks up to 30 m deep. According to the results of 2D inversion, local anomalies of low electrical resistivity mark groundwater filtration channels. In 3D geoelectrical models, pipe-like anomalies of low resistivity are identified in the areas of groundwater discharge, interpreted as filtration channels in the alluvium and the zone of exogenous fracturing in bedrock formed by sandy-clay shales, as well as linear vertical anomalies of low resistivity, interpreted as faults. On vertical sections of 3D resistive models, a connection between faults and filtration channels in alluvium and a layer of exogenous fracturing is traced. In the right bank of the valley, geoelectric signs of taliks in the bedrock, presumably associated with fault tectonics, have been established. It is assumed that the identified faults are the additional transit routes for groundwater in the Anmangynda River valley, along with the alluvial aquifer and the zone of exogenous fracturing of bedrock.